MIF-Dependent Control of Tumor Immunity - Noe, Jordan T.; Mitchell, Robert A. (Frontiers in Immunology, 2020)
Initially identified as a T lymphocyte-elicited inhibitor of macrophage motility, macrophage migration inhibitory factor (MIF) has since been found to be expressed by nearly every immune cell type examined and overexpressed in most solid and hematogenous malignant cancers. It is localized to both extracellular and intracellular compartments and physically interacts with more than a dozen different cell surface and intracellular proteins. Although classically associated with and characterized as a mediator of pro-inflammatory innate immune responses, more recent studies demonstrate that, in malignant disease settings, MIF contributes to anti-inflammatory, immune evasive, and immune tolerant phenotypes in both innate and adaptive immune cell types. This review will summarize the studies describing MIF in tumor-specific innate and adaptive immune responses and attempt to reconcile these various pleiotropic functions in normal physiology.